Guinea : Third Review Under the Three-Year Arrangement Under the Extended Credit Facility, and Financing Assurances Review-Staff Report and Press Release. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2014)
This paper discusses Guinea's Third Review under the Three-Year Arrangement under the Extended Credit Facility (ECF) and Financing Assurances Review. The macroeconomic environment in Guinea in 2013 was difficult, reflecting the fragile sociopolitical situation and a sharp slowdown in mining sector projects. As a result, growth is estimated to have slowed to 2.5 percent, sharply below the projected 4.5 percent. Inflation continued to fall and at the end of 2013 was 10.5 percent year over year. International reserves were maintained at a satisfactory level, and the exchange rate remained broadly stable. Performance under the ECF-supported program remains satisfactory. The IMF staff supports the completion of the third review under the ECF arrangement and completion of the financing assurances review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet